PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP SIKAP DAN PERILAKU KARYAWAN - Harsasi, Meirani; Anfas, Anfas (Jurnal MS, 2017)
This study aimed to analyze the effect of perceived organizational support (POS) on employee attitudes and behavior that is mediated by affective commitment. Employee attitudes and behavior shown by organizational citizenship behavior (OCB), intention to remain with the organization, and absenteeism. The study was conducted at the Universitas Terbuka (UT). The study population was all UT employees and the samples selected by using purposive sampling. Some employees at UT center and in the regions chosen as samples. A total of 248 data can be collected and analyzed further. Analysis was done gradually, through validity, reliability, and path analysis. Hypothesis test results showed that the POS positive effect on affective commitment and affective commitment influence the OCB and intention to remain with the organization. Absenteeism was found not to be influenced by affective commitment that showed that despite having high levels of affective commitment, the level of absenteeism is also a high in average.